An Observational Study on Implication of Postoperative Visceral Edema, Assessed by CT Scan, on Complications Following Bowel Resection and Anastomosis, in a Tertiary Care Hospital in Maharashtra, India - Goel, Richa; Gaidole, Rachana; Bandgar, Amol; Saha, Arup; Banerjee, J K (Journal of Society of Surgeons of Nepal, 2024)
Introduction: Surgeries involving bowel resection and anastomosis are quite common. Fluid overload, leading to tissue edema and impaired tissue perfusion, may contribute to anastomotic leak, which is one of the most dreaded complication. Methods: In our current study, CT scan, done on postoperative day-4, was used to assess visceral edema, and its effect on development of complications post bowel anastomosis and increase in value of cross section of body trunk area ≥20% was taken as an independent risk factor of severe complication. Results: Twenty three patients were enrolled in the study, 7 of them developed complications. The most common complication observed was wound infection (Clavein Dindo grade II). Only 2 patients (28.57%) had an increase in CT area >20%. Among patients who developed complications, 33.3% had an increase in CT area and 28.6% did not. Various other factors – preoperative albumin level, timing of surgery, duration of surgery – also lead to development of complications. Statistically, no significant association could be derived between the increase in CT area and development of complications. Conclusion: As per the findings of the current study, higher fluid balance was not reflected by an increase in body surface area on CT Scan. Hence, use of CT scan as a tool to assess visceral edema needs further evaluation.